Morphological parameters of abundant and threatened chondrichthyans of the northwestern Mediterranean Sea. (7th July 2014) - Barría, C.; Navarro, J.; Coll, M.; Fernandez‐Arcaya, U.; Sáez‐Liante, R.
Summary: The diversity of chondrichthyans in the Mediterranean Sea is relatively high; however, available data indicate that this group is declining in abundance and several species are becoming rare. As a result, the collection of biological data is a priority for demographic models, stock assessments, and food web analysis. In the present study, we report morphological parameters and length–weight relationships of several chondrichthyan species, both abundant and threatened, from the western Mediterranean Sea. Samples were obtained with commercial and scientific bottom trawl vessels between 2001 and 2013. A total of 893 individuals belonging to 11 families and 20 species were weighed and total lengths measured. In addition, seven species of large demersal sharks were measured and length–length relationships obtained to study the relationships between different body length measurements. All species showed positive allometric or isometric growth, except for Centroscymnus coelolepis . The results of the length–weight relationships reveal differences between the western Mediterranean and nearby areas, depending on the species studied.